Benzothiazole derivatives with varied π-conjugation: synthesis, tunable solid-state emission, and application in single-component LEDs. Issue 16 (4th April 2022) - Song, Yuwei; Hu, Lai; Cheng, Qian; Chen, Zhiyuan; Su, Huan; Liu, Hao; Liu, Rui; Zhu, Senqiang; Zhu, Hongjun
Abstract : Single-component white-light-emitting materials are highly desirable for lighting due to their negligible reabsorption, low energy-transfer loss, and stable emission spectra. Abstract : Single-component white-light-emitting materials are highly desirable for lighting due to their negligible reabsorption, low energy-transfer loss, and stable emission spectra. In this work, a series of benzothiazole derivatives (ATZ1–ATZ5 ) has been designed and synthesized. Their aggregation and photoluminescence properties are regulated by adjusting their conjugated structures. The luminous colours of these compounds are obviously different in aggregated states. In particular, ATZ2 exhibits a unique white luminous colour in the solid state with a relative balance of the double emission bands (432 nm and 526 nm), which arise from the monomers and excimers of ATZ2, respectively. The single-crystal structures of ATZ1–ATZ3 also indicate that intermolecular C–H⋯π interactions greatly affect the excimer formation. In addition, light-emitting diode (LED) devices were fabricated by putting benzothiazole derivatives over UV LED chips, in which the ATZ2 -based device shows a colour coordinate of (0.28, 0.34) and a colour rendering index (CRI) of 73. The results indicate that ATZ2 is among the simplest molecular structures for single-component WLEDs reported so far. All the results indicate that the prepared benzothiazole derivatives could be promising single-component emitting materials for LEDs.